A systematic review of LGBTQ+ identities and topics in sport leadership - O’Connell, Colleen S.; Bottino, Anna (Frontiers in Sports and Active Living, 2024)
Introduction As individuals with occupational status and power, sport leaders (e.g., coaches and athletic administrators) are responsible for enforcing cultures of inclusion within institutions of athletics. Yet, sport leaders who possess LGBTQ+ sexual identities are frequently marginalized and stigmatized by entities within and outside of athletics (e.g., athletes, parents of athletes, colleagues). Therefore, LGBTQ+ sport leaders are often faced with a challenging set of circumstances: negotiate the authenticity of their sexual orientation in the context of sport, or leave the profession entirely. Methods The purpose of this study was to conduct a systematic review of research related to LGBTQ+ sport leader experiences. Using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), research across six countries (China/Taiwan/Hong Kong, Italy, New Zealand, Norway, United Kingdom, United States) between 1997 and 2021 was analyzed. Results Themes across included studies (N = 34) describe intrapersonal experiences of LGBTQ+ sport leaders, interpersonal studies examining stakeholder attitudes (i.e., parents and athletes) toward LGBTQ+ sport leaders, and sport manager attitudes toward LGBTQ+ topics. Discussion Findings convey that sport leaders continue to face marginalization due to the presence of heterosexism and heteronormativity in athletics. Future research should continue to explore LGBTQ+ sport leader experiences, behaviors, attitudes, and identities to determine their impact on fostering inclusion and belonging within athletic spaces.